Characterization of shale–fluid interaction through a series of immersion tests and rheological studies - Samyukta Koteeswaran; Mehdi Habibpour; Jim Puckette; Jack C. Pashin; Peter E. Clark (Journal of Petroleum Exploration and Production Technology, 2018)
Abstract This paper presents qualitative techniques for evaluating shale–fluid interaction. Undesirable shale–fluid interactions lead to wellbore instability, formation damage and other problems that cost the petroleum industry millions of dollars annually. A simple desktop test method, such as immersion testing, can help production engineers choose the appropriate shale inhibitors such as salt, tetramethylammonium chloride (TMAC) and polymers that can effectively reduce the impact of oilfield fluids invading shale and causing it to swell or disperse. The swelling tendency of shale is highly dependent on clay mineralogy and other properties, such as porosity and permeability. A series of immersions tests was performed to study the combined and isolated effects of salt, TMAC, and polyacrylamide on preventing shale from becoming unstable. The merit of each fluid system in shale inhibition is probed for Woodford, Chattanooga and Pride Mountain shale. Rheology of bentonite slurries is studied with different salts and TMAC to probe their efficiency in preventing the swelling of bentonite clay. Additionally, rheology of bentonite with anionic and cationic polyacrylamide and salt is investigated.